Embrace of the serpent [videorecording (DVD)] - Guerra, Ciro, 1981-; Torres, Nilbio; Bijvoet, Jan, 1966-; Bolívar, Antonio (Actor) (Oscilloscope Laboratories, 2016)
The film centers on Karamakate, an Amazonian shaman and the last survivor of his people, and the two scientists who, over the course of 40 years, build a friendship with him. The film was inspired by the real-life journals of two explorers (Theodor Koch-Grünberg and Richard Evans Schultes) who traveled through the Colombian Amazon during the last century in search of the sacred and difficult-to-find psychedelic Yakruna plant.